2010
DOI: 10.1037/a0017344
|View full text |Cite
|
Sign up to set email alerts
|

The impact of positive mood on trust in interpersonal and intergroup interactions.

Abstract: Although the trust development literature has been characterized overwhelmingly by rationality-based models, the current research attempts to explain how affect can influence this process. To better understand how and why affect would influence trust development, 5 experiments were conducted to examine the effects of positive mood on people's tendencies to trust and distrust others. Consistent with theory, which argues that positive mood promotes schema reliance, the relationship between positive mood and trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
109
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(119 citation statements)
references
References 114 publications
(142 reference statements)
9
109
0
1
Order By: Relevance
“…They learned that the May 2010 issue of Consumer Reports Canada magazine (a fictitious magazine) reported a poll indicating that Canadian consumers gave Apollo relatively high marks in terms of design and functionality. The final information about the poll contained our trust manipulation, which built on work by Insko et al (2005) and Lount (2010). In the trust-unknown condition, participants were not exposed to any information about the company's trustworthiness.…”
Section: Materials and Procedurementioning
confidence: 99%
“…They learned that the May 2010 issue of Consumer Reports Canada magazine (a fictitious magazine) reported a poll indicating that Canadian consumers gave Apollo relatively high marks in terms of design and functionality. The final information about the poll contained our trust manipulation, which built on work by Insko et al (2005) and Lount (2010). In the trust-unknown condition, participants were not exposed to any information about the company's trustworthiness.…”
Section: Materials and Procedurementioning
confidence: 99%
“…In spite of growing interest in how trust changes over time, we know little about how characteristics of the trusting party influence reactions to untrustworthy behavior. Both personal and situational factors are critical to predicting behavior (Epstein & O'Brien, 1985;Mischel & Shoda, 1995), but trust scholars have mostly focused on situational factors, such as emotion (Dunn & Schweitzer, 2005;Lount, 2010), social status (Lount & Pettit, 2011), and timing of the trust breach (Lount et al, 2008). We extend knowledge by exploring whether gender is one important personal characteristic that influences trust following a violation.…”
mentioning
confidence: 99%
“…This stream of research investigates how incentives (Lewicki, Tomlinson, and Gillespie 2006), formal contracts (Malhotra and Murnighan 2002), reciprocity (Pillutla, Malhotra and Murnighan 2003), implicit beliefs (Haselhuhn, Schweitzer and Wood 2010), and emotions (Dunn and Schweitzer 2005;Lount 2010) influence trust. For example, Malhotra and Murnighan (2002) found that the use of contracts impeded trust development.…”
Section: Literature Review Experimental Studies Of Trustmentioning
confidence: 99%